Incorporation of forest residues on the soil: evolution and consequences in soils formed on rañas of Montes de Toledo (Spain) - Blanco, A. (Forest Systems, 1993)
In this paper the evolution of the splinters generated and incorporated to the soil as a result of several forest cultural operations are studied. To reach this goal several testing plots has been set and the effects on the soil environment has been analized.